Using the Mathermatical Models to Study the Marine Ecosystem of Binh THuan - Ninh Thuan Sea Area and Tam Giang - Cau Hai Lagoon - Bo, Doan (VNU Journal of Science: Natural Sciences and Technology; Vol 17 No 2, 2001)
Abstract